Periodontal disease and dental caries among Indigenous Australians living in the Northern Territory, Australia. (4th February 2014) - Kapellas, K; Skilton, MR; Maple‐Brown, LJ; Do, LG; Bartold, PM; O'Dea, K; Brown, A; Celermajer, DS; Jamieson, LM
Abstract Background The aim of this study was to describe the caries experience and severity of periodontal disease in a convenience sample of Indigenous Australians living in the Northern Territory. Methods Data were gathered via self‐reported questionnaire and dental examination by calibrated examiners. Socio‐demographic characteristics were compared with data from the 2011 Australian census while prevalence of periodontal disease and dental caries was compared against weighted estimates from the National Survey of Adult Oral Health 2004–2006. In each comparison, non‐overlapping 95% confidence intervals inferred a significant difference. Within‐study comparisons were assessed via chi‐square, t‐tests and analysis of variance for differences among study participants. Results A total of 312 Indigenous Australian participants provided completed data (average age 39.5 ± 10.5 years, 174 males). Of these, 87.5% were confirmed periodontitis cases; 3.5 times that of national‐level estimates. The experience of untreated caries was five times that of national estimates (mean decayed 3.0 versus 0.6). Periodontitis case status was positively associated with older age, male gender and presence of diabetes. Conclusions Periodontal disease and untreated caries were significantly more prevalent in this sample of Indigenous Australians compared to the general Australian population. The prevalence of periodontal disease was markedly higher than that previously described for Indigenous Australians.